2014
DOI: 10.1002/anie.201408211
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Change in the Nature of Chemical Bonding by Isotopic Substitution

Abstract: Isotope effects are important in the making and breaking of chemical bonds in chemical reactivity. Here we report on a new discovery, that isotopic substitution can fundamentally alter the nature of chemical bonding. This is established by systematic, rigorous quantum chemistry calculations of the isotopomers BrLBr, where L is an isotope of hydrogen. All the heavier isotopomers of BrHBr, BrDBr, BrTBr, and Br(4)HBr, the latter indicating the muonic He atom, the heaviest isotope of H, can only be stabilized as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 24 publications
7
50
1
1
Order By: Relevance
“…BrH + Br reaction [39] and used it successfully for simulation of some important properties of BrHBr À and BrDBr À [40]. In addition, we also found that the system has the ''vibrational-bonding'' bound state when the hydrogen atom is replaced by Mu atom (=muonium with a mass of 0.114 u) [40]. This result is qualitatively in accord with recent experimental observations [41,42].…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…BrH + Br reaction [39] and used it successfully for simulation of some important properties of BrHBr À and BrDBr À [40]. In addition, we also found that the system has the ''vibrational-bonding'' bound state when the hydrogen atom is replaced by Mu atom (=muonium with a mass of 0.114 u) [40]. This result is qualitatively in accord with recent experimental observations [41,42].…”
Section: Introductionsupporting
confidence: 87%
“…1 and 2, the ground state potential energy surface has a relatively deep van der Waals well with a depth of 0.076 eV, corresponding to the linear IÁ Á ÁHI van der Waals complex (C 1v ). We did not find a stable bent IÁ Á ÁHI van der Waals complex on our potential energy surface in contrast with the Br + HBr case [40,49]. Similarly, both the second and third states have linear van der Waals minima but the well depth on the third state is found to comparable to that on the ground state.…”
Section: Theorycontrasting
confidence: 68%
See 3 more Smart Citations